The Justiciability of the Right to Health: a look into the Brazilian case - Brandão Timo, Pétalla (2012)
AbstractThe increasing number of individual cases reaching courts with the view of ensuring the implementation of social rights through judicial mechanisms gave rise to highly polemic debates in different countries, prominently in the last ten years. By way of a study of the Brazilian case, the paper presents a comprehensive overview on the justiciability of the right to health, asking how the judiciary is, or at least should be, best suited to realize this guaranteed right concretely.Keywords: social rights, right to health, justiciability, Brazil.ResumenEl creciente número de casos individuales que llegan a los tribunales buscando garantizar la implementación de derechos sociales por la vía judicial ha provocado debates polémicos en diferentes países, de manera destacada en los últimos diez años. Con base en un estudio del caso brasileño, el artículo presenta un panorama general sobre la justiciabilidad del derecho a la salud, cuestionando cómo el poder judicial puede garantizar más adecuadamente la realización efectiva de este derecho.Palabras clave: derechos sociales, derecho a la salud, justiciabilidad, Brasil.